"And Who Will Write Me?": Maternalizing Networks of Remembrance in Maggie O'Farrell's Hamnet. (3rd April 2021) - O'Neill, Stephen
ABSTRACT: Maggie O'Farrell's award-winning novel Hamnet explores the tradition that the death of Shakespeare's son inaugurates the father's play. Reopening Hamlet 's metaphorical grave, the novel brings its reader into the play's imagined point of origin. It does so, this article argues, less out of an interest in Shakespeare himself or the primacy of father/son dyad than in acts of recovery that take the reader into a network of linked early modern lives. In addition to the extraordinary vitality the novel gives to the young boy, particular focus is placed on Agnes, its imagining of Anne Hathaway. Drawing on the fields of motherhood studies and memory studies, as well as Shakespeare adaptation, I argue that Hamnet creates networks of remembrance that are significantly maternalized. These include Hamlet and an epigraph citing Stephen Greenblatt's Hamnet essay, as well as memories and stories the Hamlet tradition displaces. Reading the novel through a series of interrelated themes – doubles, memories and ghosts – the article explores how O'Farrell engages with Hamlet as its inherited memory space and announces itself as a novel interested in maternal memories, spaces and stories. As such, the novel provides fascinating insight into how a literary text produces memory and invites us to remember a classic text like Hamlet differently.